MON-391 Implementation of an Osteoporosis Risk Assessment Instrument (ORAI) to Increase Referral Rates for DEXA Scanning in the Primary Care Setting - Saatciler, Eda (J Endocr Soc, 2020)
Abstract Background/Purpose: Osteoporosis (OP)was first identified and named by healthcare professionals in the 18th century. Today, OP is still the source of fractures which impair mobility, leading to sub-acute stays at rehabilitation centers. A major obstacle is that primary care providers (PCPs) fail to identify warning signs of OP, and inform patients that Dual Energy X-Ray Absorptiometry (DEXA) scans that are one of the best procedures to assess bone health. This project addressed the issue of low rate of referrals for DEXA scans. Theoretical Framework: The Knowledge-to-Action (KTA) model was used to guide this study. Intervention: Implementation of osteoporosis risk assessment instrument. Methods (Design, Sample, Setting, Measures, Analysis): This includes pre-implementation phase, patients’ charts were reviewed; post-implementation phase, the number of people referred to have DEXA scans were analyzed; the evaluation phase, results compared to the previous data. The project focus exclusively on women and men ages 50 to 89 years in two primary care offices in New Jersey. Descriptive analyses concentrated on whether or not ORAI was the tool to increase DEXA scans. Results: The data analysis reflected that the baseline referral rates increased from 1.3 % to 42 % and patients who scored high on the risk assessment instrument have been referred more often than not. Moreover, patients who are at risk and younger than 65 years of age, risk assessment tools led to a positive referral for a DEXA scan. Those who are older than 65 years, risk assessment tools like ORAI should be given with fracture risk assessment tools. This is especially the case when dealing with men, a demographic group often overlooked in the fight against OP. Conclusions Implications: If this project is to be applied at other clinics, more and more patients would be referred, raising awareness of the medical benefits of early detection. Reasonably, covering a broader section of patients, earlier in their lives, will increase clinical income, bringing more patients to primary care offices.